Size-selective ionic crosslinking provides stretchable mixed ionic-electronic conductors - Lee, Junwoo (2023)
Mechanically compliant conductors are of utmost importance for the emerging fields of soft electronics and robotics. However, the development of intrinsically deformable organic conductors remains a challenge due to the trade-off between mechanical performance and charge mobility. In this study, we report a solution to this issue based on size-selective ionic crosslinking. This rationally designed crosslinking mediated by length-regulated oligo(ethylene glycol) pendant groups and metal ions simultaneously improved the softness and toughness and ensured excellent mixed ionic–electronic conductivity in poly(3,4-ethylenedioxythiophene):polystyrene sulfonate composite materials. Moreover, the added ions remarkably promoted accumulation of charge carriers in response to temperature gradient, thus offering a viable approach to stretchable thermoelectric generators with enhanced stability against humidity.